Utilization of Various Types of Beans as Alternative Ingredients for Making Tempe in Ubedolumolo I Village, Ngada Regency - Nataniel Umbu Limbu; Antonia P. Bao (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Tempe is a processed and packaged form of ready-to-eat cuisine. For instance, tempeh chips are a popular variety of tempeh. Tempeh made from different kinds of legumes will have varied sensory and physicochemical properties. This is because the beans have different nutritional compositions, particularly with regard to protein, carbs, and lipids. The goal of this study is to experiment with producing tempeh using a variety of beans, including peanuts, red beans, black beans, cowpea seeds, and other fundamental ingredients. Training in the form of indoor practice is the method employed in this study. Panelists, specifically members of the community present at Flores Bajawa Agricultural College's Education Expo Exhibition Stand, used organoleptic tests to gather tempeh assessments from different kinds of beans. Tempeh products created from pigeon pea seeds, peanuts, red beans, and black beans have a unique taste and perfume similar to ordinary tempeh, but when consumed, they leave a little bitter aftertaste. The community recognizes the innovation. The community usually welcomes the research findings on tempeh products derived from kecipir seeds, peanuts, red beans, and black beans since they are thought to be innovative in raising the economic worth of different kinds of agricultural beans.